Faktor Yang Mempengaruhi Keputusan Mahasiswa S1 Ekonomi Islam Fakultas Ekonomi dan Bisnis Universitas Airlangga Belum Menjadi Nasabah Bank Syariah - Johan, Mega Nilasari; Ratnasari, Ririn Tri (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This research aims to determine the factors that influence the decision of Students ofÂ Islamic Economics FEB UNAIR not selected as Syariah Bankâs Customer.This research used quantitative methods through exploratory factor analysis.Â Characteristic of the research population are students of Islamic Economics UNAIR whoÂ following the active class. The number of samples in pre eliminary test by conducting aÂ written interview by 25 respondents, and main test required 100 respondents. The samplingÂ technique used is probability sampling. Sampling was done using simple random sampling.Based on the results of the study indicate that there are four factors that affect theÂ decision of Students of Islamic Economics FEB UNAIR. The four factors as a result of reductionÂ of processing factor analysis. These four factors named by factor of the brand image,Â product knowledge, spurious loyalty, service experience.Advice for the Syariah Bank are improves service experience for every remittanceÂ transactions by ontime, Syariah Bank offers interesting sales promotion to get customers,Â more socialization about negative impact of riba, not burden charge for every transactionsÂ in ATM or online banking. Advice for the next researcher, can analys factors made from thisÂ research influencing other variabel that decision muslim students S1 FEB UNAIR have notÂ been Syariah Bankâs customer yet, for the second next research, make the factors in thisÂ research being exogen variables that influenced muslim consumen behavior to SyariahÂ Bank.